2005
DOI: 10.1590/s0100-879x2005000700006
|View full text |Cite
|
Sign up to set email alerts
|

IgE expression on the surface of B1 and B2 lymphocytes in experimental murine schistosomiasis

Abstract: In a previous study we monitored the distribution and phenotype expression of B1 cells during the evolution of experimental murine schistosomiasis mansoni and we proposed that the B1 cells were heterogeneous: a fraction which originated in the spleen and followed the migratory pathway to mesenteric ganglia, while the other was the resident peritoneal B1-cell pool. In the present study, we have addressed the question of whether these two B1-lymphocyte populations are involved in the production of the late Ig is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Velupillai et al [37] have reported that B-1a cell outgrowth depends on the mouse strain during S. mansoni infection, and at early and acute infection, the frequencies of PerC B-1a cells change differently among various strains of infected mice. Besides, the percentages of splenic B-1a cells increase in C3H/HeN mice during acute and chronic S. mansoni infection [37,39]. Here, we observed that the proportions of PerC and splenic B-1a cells remained relatively constant at three weeks of S. japonicum infection, whereas these proportions were significantly reduced during acute and chronic schistosomiasis.…”
Section: Discussionmentioning
confidence: 61%
“…Velupillai et al [37] have reported that B-1a cell outgrowth depends on the mouse strain during S. mansoni infection, and at early and acute infection, the frequencies of PerC B-1a cells change differently among various strains of infected mice. Besides, the percentages of splenic B-1a cells increase in C3H/HeN mice during acute and chronic S. mansoni infection [37,39]. Here, we observed that the proportions of PerC and splenic B-1a cells remained relatively constant at three weeks of S. japonicum infection, whereas these proportions were significantly reduced during acute and chronic schistosomiasis.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we have shown that peritoneal B1 cells from S. mansoni-infected mice switch from an IgM class to an IgE class (Oliveira et al 2005) and that infected Lgals3 −/− mice present high levels of serum IgE during schistosomiasis (Oliveira et al 2007). However, we found no differences in IgE + B cells of Lgals3 +/+ and Lgals3 −/− mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soluble schistosoma-antigens and increased circulating levels of cytokines continuously stimulate peritoneal B cells during schitosomiasis (Pinho et al 2005;Weinberg et al 1992). In particular, peritoneal B1 lymphocytes have been shown to switch from IgM to IgE during S. mansoni infection (Oliveira et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, B1CD plasma cells also release “induced antibodies” or “pathogen-specific antibodies” in response to infection. A fraction of migrated B-1 cells undergo affinity maturation, increasing their specificity to the antigen ( Chen et al, 2003 ; Alugupalli et al, 2004 ) and class-switch toward IgA ( Kroese et al, 1989 ; New et al, 2020 ), IgG ( Hirose et al, 1993 ; Chen et al, 2003 ) and IgE ( Oliveira et al, 2005 ; Ghosh et al, 2012 ). These induced antibodies represent new additions to the B-1 cell repertoire.…”
Section: B-1 Cells In Pathological Conditionsmentioning
confidence: 99%